A Systemic Review of Smart Technology Sport Bras for Examining Cardiovascular Function - Natasha Sarkis; Madelyn MF Eybergen; Brook-Lyn Phelan; David M. Andrews; Andrew S. Perrotta (Journal of Kinesiology and Exercise Sciences)
Introduction: Unremitting advancements in wearable technology provides female consumers a plethora of fabricated garments that claim to monitoring biological function. Aim: This systematic review examined current literature pertaining to smart technology sport bras fabricated to assess cardiovascular function. Material and Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was utilized, and the review was registered in the International prospective register of systemic reviews (PROSPERO) within the National Institute for Health and Care Research (NIHR). A total of 949 articles were screened after using key search terms using the Covidence systematic review software. Articles were sourced from PubMed, SPORTDiscus, or Medline via OVID databases. Results: A total of 19 articles were examined for eligibility and was reduced to a total of three articles to be included in the review. The results from this systematic review highlight the paucity of commercially available sport bras capable of accurately examining cardiovascular function during rest and exercise, while concomitantly providing the necessary support and comfort requirements for females. Of the commercially available sport bras, the Berlei sport bras was identified as the most accurate for recording cardiovascular stress during resting, walking, and running conditions. The three studies included in this review demonstrate strong potential for washable and flexible e-textile sensors with sufficient accuracy in pressure ranges that can be used in sport bras to monitor biological functioning. Conclusions: Future research should prioritize enhancing participant diversity in the examination of smart sport bras to ensure comprehensive inclusion of all body types.